PENGARUH TINGKAT PENGUNGKAPAN SUKARELA TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL KONTROL LEVERAGE, GROWTH, SIZE, DAN ROA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - Siti Rabiatul Fauziah; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2020)
The study aims to examine empirical evidence affecting voluntary disclosure rates with control variables of leverage, growth, size, and ROA at the company's value. This method uses quantitative methods. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2016-2019.Sample selection using purposive sampling. A sample of 53 companies with a four-year observation, resulting in a total test sample is 212 observations. Data types use secondary data, data analysis uses multiple linear regression, test normality, classic assumption test and hypothesis testing.The results of this study showed that the partial hypothesis of voluntary disclosure rates, leverage, growth, size, and ROA had a significant impact on the company's value. For simultaneous testing between voluntary disclosure rates, leverage, growth, size, and ROA have an influence on the company's valueKeywords: voluntary disclosure rate, leverage, growth, size, ROA and productive company value.